Degradation of Air vs. Quality of Life – Spatial Panel Analysis - Antczak, Elżbieta (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The main purpose of the paper is to identify and analyse a correlation between excessive air pollution, well-being and the cost of living. The analysis was performed using spatial panel models. Two research hypotheses were confirmed. One assumed a negative impact of excessive air degradation on the level of socio-economic development. The other concerned an increase in the cost of living due to air pollution. 32 selected European countries were studied from 1990 to 2009. The level of socio-economic well-being was expressed by measures of the GDP per capita and HDI The cost of living was presented by means of a measure designed by the author – COSTS. Air quality was expressed in terms of S02, CO, NOx, GHG, C02 and a constructed synthetic measure – AIRQ.